Penetapan Ambang Batas Calon Presiden dan Wakil Presiden Berdasarkan UU No. 23 Tahun 2003 dan UU No. 7 Tahun 2017 - luken ferisman lubis; Eddy Asnawi; Bagio Kadaryanto (Universitas Medan Area, 2023)
The purpose of this study is how the threshold for the nomination of president and vice president is based UU No. 23 Year 2003 and UU No. 7 Year 2017 and how ideally the threshold for presidential and vice presidential candidates is determined based on UU No. 23 Year 2003 and UU No. 7 Year 2017. This type of research is normative legal research by analyzing cases that conflict with the law using qualitative methods to draw deductive conclusions. The provisions for setting thresholds in presidential elections constitutionally violate the constitutional rights of citizens based on the provisions of Article 6A paragraph (2) of the 1945 Constitution which states